2012
DOI: 10.3390/ijms14010515
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Receptor Is a Possible Target against Growth of Metastasized Lung Tumor Cells in the Brain

Abstract: In the animal model of brain metastasis using human lung squamous cell carcinoma-derived cells (HARA-B) inoculated into the left ventricle of the heart of nude mice, metastasized tumor cells and brain resident cells interact with each other. Among them, tumor cells and astrocytes have been reported to stimulate each other, releasing soluble factors from both sides, subsequently promoting tumor growth significantly. Among the receptors for soluble factors released from astrocytes, only IL-6 receptor (IL-6R) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Each of these cytokines would be expected to produce complex phenotypes in addition to BBB/BTB permeability, including myeloid, dendritic cell and lymphocyte recruitment 55 , 57 – 59 , neuronal and neural stem cell function 60 62 , and cognition 63 . A beneficial drug permeability effect of CCL2 or IL-6 must outweigh potential tumor stimulatory pathways 64 , 65 . Lung cancer lines including a brain-derived variant were insensitive to IL-6, but the extent of this resistance profile is unknown 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Each of these cytokines would be expected to produce complex phenotypes in addition to BBB/BTB permeability, including myeloid, dendritic cell and lymphocyte recruitment 55 , 57 – 59 , neuronal and neural stem cell function 60 62 , and cognition 63 . A beneficial drug permeability effect of CCL2 or IL-6 must outweigh potential tumor stimulatory pathways 64 , 65 . Lung cancer lines including a brain-derived variant were insensitive to IL-6, but the extent of this resistance profile is unknown 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines expressed by glioma cells, like IL‐6, IL‐8, and VEGF, determine a wide variety of effects like promotion of tumor cell invasion, proliferation, migration, neo‐ angiogenesis and immune cell infiltration. Specifically, IL‐6 is a pleiotropic cytokine that contributes to malignant progression and apoptosis resistance of different tumors (Noda et al, ). Il‐6 act by forming a complex with IL‐6R alpha and a transmembrane glycoprotein called gp130 lead to the activation of the signal transducer and activator of transcription (STATs) able to induce cellular transformation of fibroblasts and tumor growth in GBM cells (Heinrich, Behrmann, Müller‐Newen, Schaper, & Graeve, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the role of IL-6 in NSCLC and suggested that it promotes tumor growth and survival ( 10 12 ). Increased expression of IL-6R in human LUSC-derived cells (HARA-B) has been shown in vitro ( 13 ) and in a murine model of brain metastasis ( 14 ). Tocilizumab is an anti-IL-6R antibody, upon application, the stimulated growth of HARA-B cells was significantly inhibited and when it was injected to the animal model, the volume of metastatic focus was significantly smaller ( 14 ).…”
Section: Introductionmentioning
confidence: 99%